(untitled) (UNED Research Journal, 2020)
Introduction: Educational materials for distance education require pedagogical strategies to mediate between students and the learning content.. Objective: To analyze pedagogical strategies of the didactic materials of a university from three educational approaches. Methods: We analyzed, through a questionnaire, 31 didactic books in the areas of Health, Accounting, Human Rights, Education, Statistics, Math, Marketing, Agronomy, Natural Resources Management, English, Criminology, Chemistry and Psychology. Results: In 90% of the materials, the editors and authors apply schemes, daily life problem solving, self-evaluation exercises, explicative speech and learning objectives. In 70% we identified argumentative discourse, reflection on the learning, signalers, icons, pedagogical orientations, illustrations and incentives to self-regulation. The strategies that are seldom used are KWL charts, timelines, analogies, flowcharts, collaborative work, double column tables, advanced organizers, auxiliary columns and synoptic tables. Conclusions: The most widely used strategies favor the construction of meaningful learning, self-regulation and self-evaluation. We recommend to analyze the strategies used under 70% to identify its relevance.